Chemistry Study and Entrepreneurship Program for the younger generation at Sanggar Bimbingan Sentul, Kuala Lumpur Malaysia - Wijaya, Anugrah Ricky; Syah, Alif Alfarisyi; Putra, Helwani Fuadi Sujoko; Kusumaningrum, Irma Kartika; Pramesti, Indah Nur (J-PEK (Jurnal Pembelajaran Kimia), 2023)
The issues faced by the sons and daughters of Indonesian citizens (WNI) in Malaysia are social inequality, access to education, and a sense of community involvement. Sanggar Bimbingan Sentul, as a partner, provides learning facilities for WNI's children to solve these three main problems. We initiated to apply the program of MAWIRAKI (Matahari Kewirausahan Kimia) with chemistry study and entrepreneurship program through the Pengabdian Kemitraan Luar Negeri (PKLN) grant by Universitas Negeri Malang (UM). This program integrated by computer training with MS-Word and Paint programs, chemistry daily-life experiments, and the art of batik craft. The results of learning process WNI's children shows that 18 favored students in the Paint program and 10 in the MS Word program during computer training. The "Where's Vitamin C" experiment garnered support from 17 students, highlighting an interest in chemistry study. These activities involved the batik ecoprint and jumput, which received a positive response, with 15 students favoring batik jumputan and 11 choosing batik ecoprint. The WNI's children interest data during the learning process as the foundation and our spirit for developing programs to unearth the entrepreneurial potential and creativity of the younger generation.